2013 Canadian Hypertension Education Program Recommendations - Vinall, Phil (MD Conference Express, 2013)
While the 2013 Joint National Committee Guidelines for the Management of High Blood Pressure in adults still under revision and not available for discussion, this article discusses new and important recommendations from the Canadian Hypertension Education Program [Daskalopoulou SS et al. Can J Cardiol 2012].